Program Evaluation of a Home Visiting Program: Perspectives of Home Visitors. (November 2020) - Gudger, Kaitlin; Cartagena, Diana; Lowe, Kelsi
Abstract : The purpose of this program evaluation was to determine if home visitors at the Child Development Resources (CDR) home visiting program perceived themselves to have adequate knowledge and resources to support the goals of the program. In addition, we aimed to determine what home visitors found to be facilitators and barriers to a successful program. The project was conducted with a convenience sample of 18 home visitors and included the following instruments: (a) demographics survey, (b) CDR Home Visiting Program Survey, and (c) Breastfeeding Knowledge Questionnaire. Results suggest (a) most of the home visitors believed they had adequate resources and knowledge necessary to support families and children, (b) some perceived barriers to carrying out goals of the home visiting program were financial limitations, lack of internet and mobile devices in many homes, and perception that programs were not designed for families with significant stressors such as poverty and mental health difficulties, (c) most of the home visitors believed their families benefit from their visiting programs, but many did not overwhelmingly feel new technology would greatly help families during home visits, and (d) most home visitors appeared to have adequate breastfeeding knowledge, however, some suggested that additional breastfeeding education would be beneficial. The information gathered from this project can be used to inform and improve home visiting programs seeking to enhance the quality of their programs which will ultimately contribute to better health outcomes for at-risk mothers and children.